Comparison of Human Resource Management Characteristics between Public Sector and Private Sector in Indonesia in the Era of Digital Transformation - Mulyani, Sri; Rulandari, Novianita (Indonesian Scientific Publication, 2024)
This study compares human resource management (HRM) characteristics between Indonesia's public and private sectors in the context of digital transformation. Both sectors face increasing complexity due to digitalization and changing work paradigms. The private sector contributes 58.2% to GDP, while 68% of 4.2 million civil servants face a mismatch between competencies and job demands. The study aims to analyze the differences, challenges, and opportunities in HRM, focusing on regulatory aspects, management practices, and their impact on organizational performance. The novelty lies in the comparative approach that integrates digital transformation in HRM analysis, which has been underexplored in previous studies. Using a qualitative methodology, the research analyzes academic literature and policy documents from 2019-2024, with constant comparative analysis and source triangulation for validity. The findings reveal significant differences in organizational orientation, regulation, recruitment, motivation, and accountability. The public sector focuses on stability and regulatory compliance, while the private sector prioritizes flexibility and adaptability. This study offers theoretical implications for a new conceptual framework in comparative HRD studies and practical recommendations for optimizing HRD in the digital era, such as developing an integrated talent management system, reforming compensation policies, and strengthening cross-sector collaboration. Limitations include the study's geographic and temporal scope, suggesting further research with mixed-methods and longitudinal approaches to explore HRD practices and technological evolution. This study contributes to understanding HRD dynamics and informs the development of adaptive HRD policies in the digital age.